2003
DOI: 10.1242/dev.00773
|View full text |Cite
|
Sign up to set email alerts
|

Egfr signalling defines a protective function for ommatidial orientation in theDrosophilaeye

Abstract: Ommatidial rotation in the Drosophila eye provides a striking example of the precision with which tissue patterning can be achieved. Ommatidia in the adult eye are aligned at right angles to the equator, with dorsal and ventral ommatidia pointing in opposite directions. This pattern is established during disc development, when clusters rotate through 90°, a process dependent on planar cell polarity and rotation-specific factors such as Nemo and Scabrous. Here, we demonstrate a requirement for epidermal growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 62 publications
3
77
1
Order By: Relevance
“…In the eye, Fz/PCP signaling, together with the Notch pathway, is responsible for R3/R4 fate induction and thus for the establishment of ommatidial chirality (Cooper and Bray, 1999;Fanto and Mlodzik, 1999;Tomlinson and Struhl, 1999). Besides, it has been shown that the ommatidial rotation, depends on the Egfr pathway (Brown and Freeman, 2003;Gaengel and Mlodzik, 2003;Strutt and Strutt, 2003). Moreover, downstream of Egfr there is a requirement for the Ras/MAPK cascade and Canoe, an adherensjunction-associated protein (Young et al, 1993), that provides a link from Egfr to cytoskeletal elements (Gaengel and Mlodzik, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the eye, Fz/PCP signaling, together with the Notch pathway, is responsible for R3/R4 fate induction and thus for the establishment of ommatidial chirality (Cooper and Bray, 1999;Fanto and Mlodzik, 1999;Tomlinson and Struhl, 1999). Besides, it has been shown that the ommatidial rotation, depends on the Egfr pathway (Brown and Freeman, 2003;Gaengel and Mlodzik, 2003;Strutt and Strutt, 2003). Moreover, downstream of Egfr there is a requirement for the Ras/MAPK cascade and Canoe, an adherensjunction-associated protein (Young et al, 1993), that provides a link from Egfr to cytoskeletal elements (Gaengel and Mlodzik, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Egfr signaling promotes rotation via the Ras/Cno and Ras/Mapk/Pnt effectors (Brown and Freeman, 2003;Gaengel and Mlodzik, 2003), so its output must be dampened to slow rotation. Ed binds and inhibits the Egf receptor (Bai et al, 2001;Rawlins et al, 2003;Spencer and Cagan, 2003), whereas Fred binds Ed and interferes with this inhibition (S.A.S., unpublished).…”
Section: Research Articlementioning
confidence: 99%
“…Although mosaic analyses indicate a requirement for the PCP genes in specifying the R3 and R4 cell fates and additional work demonstrates a tight link between fate specification and the direction of rotation, the mechanisms that control the degree to which ommatidia rotate are poorly understood (Fanto and Mlodzik, 1999;Strutt et al, 2002;Wolff and Rubin, 1998). The identification of several proteins that affect only the degree of rotation, including the serine/threonine kinase Nemo (Nmo), Ecadherin (Shotgun -FlyBase), N-cadherin and members of the Egfr signaling pathway (Brown and Freeman, 2003;Choi and Benzer, 1994;Fiehler and Wolff, 2008;Gaengel and Mlodzik, 2003;Mirkovic and Mlodzik, 2006;Strutt and Strutt, 2003), suggests that a subset of genes might act to regulate this event.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations